Serotonergic receptor blockade in the lateral parabrachial nucleus: Different effects on hypertonic and isotonic NaCl intake - David, Richard B. [UNESP]; Menani, José Vanderlei [UNESP]; De Luca, Laurival A. [UNESP] (Elsevier B.V., 2008)
Hypertonic NaCl intake is produced by serotonin receptor antagonism in the lateral parabrachial nucleus (LPBN) of dehydrated rats or in rats pretreated with a mineralocorticoid, for example deoxycorticosterone (DOCA), that receive an intracerebroventricular injection (icv) of angiotensin II (ang II). The objective of the present work was to find out whether these two mechanisms are also involved with isotonic NaCl intake. Serotonin receptor blockade by methysergide in the LPBN (4 mu g/0.2 mu l bilaterally) had no effect on 0.15 M NaCl (methysergide: 19.3 +/- 5.2 ml/60 min; vehicle: 19.3 +/- 4.2 ml/60 min; n=7) or water (methysergide: 3.4 +/- 1.4 ml/ 60 min; vehicle 2.2 +/- 0.6 ml/60 min) intake induced by systemic diuretic furosemide combined with low dose of captopril (Furo/Cap). Methysergide treatment 4 days later in the same animals produced the expected enhancement in the 0.3 M NaCl intake induced by Furo/Cap (methysergide: 16.6 +/- 3.5 ml/60 min; vehicle: 6.6 +/- 1.5 ml/60 min). Similar result was obtained when another group was tested first with 0.3 M NaCl and later with 0.15 M NaCl. Isotonic NaCl intake induced by icv ang II was however enhanced by prior DOCA treatment. A de novo hypertonic NaCl intake was produced in another group by the same combined treatment. The results suggest that a facilitatory mechanism like the mineralocorticoid/ang II synergy may enhance NaCl solution intake at different levels of tonicity, while the action of an inhibitory mechanism, like the LPBN serotonergic system, is restricted to the ingestion at hypertonic levels. (c) 2007 Elsevier B.V. All rights reserved.
Keywords: dehydration; sodium appetite; serotonin; mineral intake; preference; thirst